Qualidade física de um latossolo vermelho férrico sob sistemas de uso e manejo - Carvalho Filho, Alberto; Carvalho, Luís Carlos Cirilo; Centurion, José Frederico [UNESP]; Beutler, Amauri Nelson; Cortez, Jorge Wilson; Ribon, Adriana Aparecida (My University, 2009)
The soil physical quality is defined as the soil capacity to maintain the sustainable productivity during the years. To assess soil physical quality, attributes were evaluated in the layers of 0.0-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40 m in acrustox. The experimental design was entirely randomized, with four systems of use (corn, sugar-cane, pasture and native vegetation), four soil depths and four replications. The parameter evaluated were: texture, degree of clay flocculation, soil bulk density, porosity, water retention and S parameter. The usage and management systems caused soil physical degradation, being greater in pasture system with intensive usage, with smaller soil physical quality for plants development. The soil physical quality, evaluated by physical attributes, followed the following order: native vegetation > maize > sugar-cane > pasture. The Oxisol, although shows present excellent physical structure and needs an adequate management to prevent excessive compaction.
Physical quality of an acrustox under usage systems
Keywords: Parameters S; Porosity; Soil water content